Description of Fulfillment of Demand for Blood Products at the PMI Yogyakarta City Blood Donor Unit in 2022 - Arliana Azizah; Nur'Aini Purnamaningsih; Dwi Eni Danarsih (Jurnal Kesehatan, 2023)
Introduction: The fulfillment of blood demand is very important in improving the quality of health services because it is related to the safety of other people's lives and the need for blood continues to increase every year as the population increases. Methods: This study was a quantitative descriptive study with a retrospective approach. The population and sample in this study were all blood requests totaling 44,232 at Blood Donation Unit PMI Yogyakarta City in 2022. Sampling techniques used total sampling. Data analysis was descriptive. Results: The number of requests for blood from blood donation unit PMI Yogyakarta City in 2022 was 44,232, most of which were for blood type O as many as 17,048 (38.54%), positive rhesus blood type as many as 44,186 (99.89%), and Packed Red Cell blood components as many as 34,697 (78.44%). The number of blood requests that can be fulfilled the most is blood type O as much as 16,498 (96.77%), positive rhesus blood type as much as 41,823 (94.65%), and Packed Red Cell blood components as much as 33,295 (95.96%). The most unfulfilled blood requests are blood type B as much as 922 (6.99%), negative rhesus blood type as much as 3 (6.52%), type of Washed Erytrocyte blood component as much as 2 (22.22%). Conclusion: The fulfillment of blood requests at UDD PMI Yogyakarta City that can be fulfilled is 42,268 (95.56%) of the total number of requests of 44,232 blood requests.